Clinical communication training in medical education : a conversation analytic approach - Ng, Gim Thia (2019)
Good clinical communication is increasingly recognised as pivotal to the success of medical practice, with much research having shown that the quality of communication greatly influences such factors as patient satisfaction and eventual health outcomes. Yet while communication skills training has already been widely incorporated into the curricula of medical schools around the world, doctors and other healthcare practitioners have mindsets so deeply entrenched in biomedicine that the human dimension continues to be side-lined in healthcare delivery. It is no wonder, then, that clinicians continue to struggle in their medical interactions on an everyday basis, despite the increased focus on patient-centred care globally. By examining clinical communication training with simulated patients (SP) in a young medical school in Singapore, this thesis aims to reflect and reflect upon the current efforts of medical educators endeavouring in the field. Video recordings of SP-based simulation training were collected from the school’s Clinical Communication Practicum for third-year undergraduate medical students. Using the emic, qualitative methodology of Conversation Analysis, these interactions were analysed via detailed inspection of the video data aided by transcriptions made from these recordings according to Jeffersonian conventions. Comprising a total of six simulated scenarios and 18 students, over five hours of footage was transcribed and analysed from a larger corpus of twice the size. Each session encompasses a simulated consultation between a student and an SP, as well as a facilitator-led feedback discussion involving both parties and other students. A scrutiny of the simulated consultations shows that the delivery and explanation of patient diagnoses and/or conditions follow largely similar trajectories. Students begin by first stating their intent, before attempting to establish the SP’s prior knowledge about the diagnosis/condition. Leveraging on this in the actual delivery, they then give an account of its causes and symptoms. Later, in explaining the diagnostic and/or treatment plan, they often make use of strategies such as signposting to construct a methodical framework. Nevertheless, the overall organisation of the consultation ultimately varies according to the scenario in question. Two scenarios that are considerably different from the rest separately required students to dissuade an SP against hospital discharge and persuade a senior colleague to conduct a diagnostic test. Across the board, however, the students’ consultations are characterised by two pervasive features: (1) an orientation towards information sharing over empathic understanding, and (2) an inadequacy in their calibration of language use. The feedback discussion then commences after the simulated consultation is complete. Facilitators guide this second segment using Pendleton’s rules as the adopted framework, which required them to garner feedback from all participants in terms of “what was done well” and “what could be improved”. The analysis shows this structured approach as both a boon and a bane for student learning. While facilitators’ stringent adherence to the rules ensure that students receive feedback from all parties, it subjects the discussion to a rigid configuration that limits input to certain forms which may otherwise turn out more substantial with free debate. On the other hand, when facilitators do not formulate their guiding prompts in a manner that clearly demarcates the two questions, feedback received is either imbalanced or imprecise. Skilful use of the rules in facilitation is therefore needed to ensure that students receive (and themselves produce) rich feedback that enhances their learning. From the various findings, recommendations have been made to improve the teaching and learning of clinical communication in medical education. These target the design of the scenarios, representations made by SPs and students, the role of facilitators, and the use of the data as teaching materials. Nonetheless, caution must be exercised in implementation to ensure that these suggestions do not culminate in yet another prescriptive framework, but instead benefit SP training participants by raising their awareness of different conversational approaches and aiding them in deploying their own strategies of handling clinical interactions.